Analisis Peran Zakat Produktif dalam Meningkatkan Pendapatan Usaha Mikro : (Studi Kasus: Badan Amil Zakat Nasional (BAZNAS) Kota Bukittinggi) - Putri Nadhila Maulani; Aidil Alfin (Universitas 45 Surabaya, 2024)
The efficiency of productive zakat funds in boosting the revenue of microbusinesses in Bukittinggi City as capital for proprietors who need extra cash to grow their enterprises serves as the driving force behind this study. Aside from that, the Bukittinggi City BAZNAS institution's method of allocating productive zakat payments to microbusiness actors who have been granted Productive Zakat is less successful. Research methodologies used in this study include qualitative and field research. Research that visits the field itself to get data directly from sources is known as field research. Qualitative research, on the other hand, aims to provide a descriptive description of speech, writing, or observable behavior. The study's findings demonstrate the usefulness of productive zakat in raising BAZNAS Bukittinggi City's microbusiness revenue. The Bukittinggi City BAZNAS Institute's strategy for increasing the effectiveness of the distribution of productive zakat monies involves teaching donors at the time of zakat fund transfer without any further monitoring or assessment.